Three-dimensional analysis of mandibular and condylar growth using artificial intelligence tools: a comparison of twin-block and Frankel II Appliances - Ramy Shihabi; YiSi Liu; Abdalrahman Mohieddin Kusaibati; Fakhr Maraabeh; Jiaqi Zhan; Jiaqi Zhang; Li Hu (BMC Oral Health)
Abstract Background Analyzing the morphological growth changes upon mandibular advancement between Twin Block (TB) and Functional Regulator II (FR2) in Class II patients involves measuring the condylar and mandibular changes in terms of linear and volumetric measurements, as well as the distances registered after superimposition. Correspondingly, 3D digital assessment with the benefit of artificial intelligence tools was applied, and color-coded distance maps were descriptively interpreted to visualize the direction of growth. Subjects and methods Twenty patients aged 9 to 12 years with skeletal Class II malocclusion with overjet (5–9 mm) were enrolled into two groups: Group 1 (TB) and Group 2 (FR2). CBCT radiographs were taken at T0 (prior to treatment) and T1 (at the end of effective treatment; 7–11 months). 3D UX-Net algorithm was used to extract the 3D models and obtain the volumes. Visual Basic software was employed to develop a method for calculating the 3D distances and angles. 3D superimposition methods through Viewbox software were utilized to analyze growth direction following the treatments, using color-coded distance map visualizations. Results The average volume increase of the mandible, right and left condyle was 2666.00 ± 1469.16 mm³, 207.70 ± 125.28 mm³, and 216.90 ± 121.65 mm³, respectively, after TB treatment, and 3316.10 ± 1552.29 mm³, 208.90 ± 116.85 mm³, and 193.65 ± 114.25 mm³, respectively, after FR2 treatment. The mean absolute distances (MAD) for the mandible, right, and left condyle from T1 to T0 were in TB group 1.238 ± 0.757 mm, 2.248 ± 0.346 mm, 2.267 ± 0.593 mm, respectively, and in FR2 group 1.417 ± 0.550 mm, 2.616 ± 1.063 mm, 2.475 ± 0.916 mm, respectively. The visualization of color-coded maps revealed a superior-posterior growth direction of the condyle measuring within 3 mm after the treatment. Conclusions Although mandibular and condylar volumes increased in each group when comparing T0 to T1, indicating the efficacy of both appliances in enhancing growth, no clinically or statistically significant differences were observed between the groups in terms of volumetric, linear, and 3D superimposition changes. However, color-coded distance maps demonstrated a consistent pattern of posterior-superior relocation of the condyles in most cases after treatment when comparing T1 to T0, whereas the back of the ramus in more than half of the cases has moved backwards. With no statistical differences between the studied groups.